2020
DOI: 10.3390/economies8040104
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns in Fiscal Impacts of Environmental Taxation in the EU

Abstract: There are several reasons for environmental taxation implementation. Besides its environmental impact, the main reason for such taxation is its fiscal impact, particularly in generating revenues of public budgets. The main goal of this paper is to observe possible spatial patterns in fiscal impacts of environmental taxation in the EU countries, and to depict the groups of countries with the same (or similar) fiscal impact of these instruments on public budget revenues, including environmental and economic char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
1
0
2
Order By: Relevance
“…La gama de instrumentos incluye, entre otros, impuestos ambientales, tarifas, cargos, permisos negociables, sistemas de depósito-reembolso y subsidios. La UE ha favorecido cada vez más este tipo de instrumentos porque proporcionan medios flexibles y rentables para reforzar el principio de quien contamina paga, además auxilian el alcance de los objetivos de la política medioambiental (Pászto et al, 2020).…”
Section: La Fiscalidad Ambiental De La Unión Europeaunclassified
See 1 more Smart Citation
“…La gama de instrumentos incluye, entre otros, impuestos ambientales, tarifas, cargos, permisos negociables, sistemas de depósito-reembolso y subsidios. La UE ha favorecido cada vez más este tipo de instrumentos porque proporcionan medios flexibles y rentables para reforzar el principio de quien contamina paga, además auxilian el alcance de los objetivos de la política medioambiental (Pászto et al, 2020).…”
Section: La Fiscalidad Ambiental De La Unión Europeaunclassified
“…La fiscalidad ambiental es un instrumento jurídico-económico de la política ambiental que hace referencia al conjunto de medidas tributarias que buscan crear un modelo económico más eficiente y, a su vez, proteger el medio ambiente. En ella se incluye tanto figuras impositivas que gravan las actividades perjudiciales al medio como son impuestos ecológicos, tasas, cánones, etc., como incentivos fiscales, tales como reducciones, bonificaciones, deducciones de impuestos ordinarios con el fin de premiar aquellos comportamientos amables con el medio ambiente (Pászto et al, 2020). Por lo tanto, mediante la creación figuras tributarias, los gobiernos han establecido un gravamen a aquellas externalidades que afectan de forma negativa al medioambiente con la intención de proteger y conservar el medio ambiente (Atkinson, 2005).…”
Section: La Fiscalidad Ambiental De La Unión Europeaunclassified
“…However, the overall environmental tax rate for transportation vehicles is low, or sometimes not. It is recommended that environmental taxes increase the tax rate and increase the collection of traffic pollution [18]. López Pérez et al, (2021) found that since 2014, Mexico has levied environmental taxes in a small range and extremely low carbon emission prices, resulting in less income from environmental taxes.…”
Section: Brief Literature Reviewmentioning
confidence: 99%